Total Quality Management and its relationship to competitive advantage in libraries and documentation centers - dayah, salah; Sidhoum, khalida (Journal of Social Sciences and Humanities, 2022)
This study aims to highlight the relationship between total quality management and the competitive advantage of libraries and documentation centers. In order to achieve this objective, we have used the descriptive analytical approach in the enumeration of information and facts, we have indeed addressed: the concept of total quality management, the basic principles on which libraries and documentation centres are relied, and then the significance and importance of competitive advantage; and the mechanisms for applying it within libraries and documentation centers , This is followed by an explanation of the relationship dimensions between total quality management and competitive advantage. The study produced a series of results, the most important of which is that total quality management for libraries and documentation centers has become a fundamental objective of their modern administrations, aware of their importance in holding the competitive advantage that will ensure their survival, sustainability and competitiveness; and confer recognition and prestige on them.